1985
DOI: 10.1042/cs0690273
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plasma volume, in transcapillary escape rate of albumin and in subcutaneous blood flow during hypoglycaemia in man

Abstract: Hypoglycaemia was induced by insulin injected intravenously (0.15 i.u./kg body weight) in seven healthy young males. Plasma volume was measured before and during hypoglycaemia by intravenous injection of 125I before hypoglycaemia and of 131I during hypoglycaemia. Plasma volume decreased and transcapillary escape rate increased significantly during hypoglycaemia. Skin temperature and local subcutaneous adipose tissue blood flow were measured in four different regions. Both tended to decrease during hypoglycaemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…13 Furthermore, additional effects due to alterations in subcutaneous blood flow during hypoglycemia cannot be ruled out, although an increase and a decrease during hypoglycaemia have both been described. [15][16][17][18] Finally, it may also be argued that, because of measurement errors, home fingerstick capillary blood glucose levels are not always representative for plasma blood glucose levels. [19][20][21] Several reports have cast doubt on the accuracy of home monitoring devices in pregnant women with diabetes with glucose levels ranging up to 8.0 mmol/L.…”
Section: Discussionmentioning
confidence: 97%
“…13 Furthermore, additional effects due to alterations in subcutaneous blood flow during hypoglycemia cannot be ruled out, although an increase and a decrease during hypoglycaemia have both been described. [15][16][17][18] Finally, it may also be argued that, because of measurement errors, home fingerstick capillary blood glucose levels are not always representative for plasma blood glucose levels. [19][20][21] Several reports have cast doubt on the accuracy of home monitoring devices in pregnant women with diabetes with glucose levels ranging up to 8.0 mmol/L.…”
Section: Discussionmentioning
confidence: 97%
“…Erythrocytes Experimental studies of acute hypoglycaemia have demonstrated a modest increase in the number of circulating erythrocytes in relation to the peak of plasma epinephrine concentration in response to the hypoglycaemic stimulus [80,81]. This apparent erythrocytosis is probably a manifestation of haemo-concentration and a rise in packed cell volume rather than the entry of red blood cells into the circulation from storage sites, as this response is preserved in people who have undergone previous splenectomy [82].…”
Section: Constituents Of Bloodmentioning
confidence: 96%
“…In a study by Hilsted et al. (), a decrease in subcutaneous ATBF was found during hypoglycemia (~2 mmol/L), induced by insulin injected intravenously. This vasoconstriction was probably due to stimulation of vascular α ‐receptors by increased circulating catecholamines.…”
Section: Discussionmentioning
confidence: 91%
“…Altogether, indicating that a significant activation of the sympathetic nervous system was probably not induced in this study by the transient decrease in blood glucose levels induced by GLP-1. In a study by Hilsted et al (1985), a decrease in subcutaneous ATBF was found during hypoglycemia (~2 mmol/L), induced by insulin injected intravenously. This vasoconstriction was probably due to stimulation of vascular a-receptors by increased circulating catecholamines.…”
Section: Discussionmentioning
confidence: 95%